Chest CT features of coronavirus disease 2019 (COVID-19) in pediatric patients and its correlation with the clinical condition - Abeer El-Sayed Gabr; Abeer Maghawry Abdelhameed; Shaimaa Abdelsattar Mohammad; Eman Mahmoud Fouda; Shimaa Ahmed Maher; Samah Khalaf Fathallah; Mona Gamalludin Alsayed Muhammed Alkaphoury (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background All pediatric health organizations are concerned about the impact of coronavirus disease on children, especially on those with other comorbidities; fortunately, pediatric cases appear to be less severe than in adults (De Luca et al. in Pediatr Respir Rev 5:9–14, 2020). The purpose of this study is to characterize chest CT findings of children with and without comorbidities who had confirmed coronavirus disease (COVID-19) and to investigate the relation between chest CT findings and the clinical severity of COVID-19 pneumonia and their laboratory findings. Results The study was conducted on 36 patients, 72.2% of whom had associated comorbidities. Twenty-three patients (63.88%) had abnormal CT findings. Consolidative patches were the most common radiological sign (55.6%) followed by ground glass opacities (50%). The lesions were bilateral (58.3%), having predominantly peripheral distribution (38.9%) with predominant left lower lobe affection (25%). Cases with clinically severe chest conditions had significantly more prevalent consolidative patches (p = 0.026) which show a higher CT density (p = 0.01) and a significantly higher CT severity score (SS) compared to other groups (p = 0.029). The cutoff of severity score 4/20 had 100% sensitivity and 78.12% specificity in the diagnosis of severe cases. There were no statistically significant differences between patients with or without comorbidities regarding CT-SS or any radiological signs. Conclusions Consolidation was the most common radiological finding in children with COVID-19 and was more prevalent and denser in severe cases. The CT-SS may be used as a complementary tool for the evaluation of the severity of the chest condition. Chest CT-SS more than 4 can be used as an indicator of severe cases, yet no significant difference in CT-SS between patients with associated comorbidities or not.